2019
DOI: 10.1534/g3.119.400103
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Complex Genetics of Karnal Bunt (Tilletia indica) Resistance in Common Wheat (Triticum aestivum) by Genetic Linkage and Genome-Wide Association Analyses

Abstract: Karnal bunt caused by Tilletia indica Mitra [syn. Neovossia indica (Mitra) Mundkur] is a significant biosecurity concern for wheat-exporting countries that are free of the disease. It is a seed-, soil-and air-borne disease with no effective chemical control measures. The current study used data from multi-year field experiments of two bi-parental populations and a genome-wide association (GWA) mapping panel to unravel the genetic basis for resistance in common whea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 62 publications
5
21
0
Order By: Relevance
“…The results of the current study validated the consensus region on chromosome 3B reported in previous studies 2,15 (Fig. 4).…”
Section: Linkage Disequilibrium Analysis and Genome-wide Association supporting
confidence: 91%
See 3 more Smart Citations
“…The results of the current study validated the consensus region on chromosome 3B reported in previous studies 2,15 (Fig. 4).…”
Section: Linkage Disequilibrium Analysis and Genome-wide Association supporting
confidence: 91%
“…Similar results were recorded during QTL mapping for KB resistance in two different studies 2,8 . The heritability of trait was high in both years (91% and 87% in E-1 and E-2, respectively) (Supplementary Table S3), suggesting that KB resistance can be mapped through QTL mapping and GWAS 2,15 . The phenotyping protocols established at CENEB, Cd.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The wealth of genomic information available for important crops has enabled the use of marker data for molecular breeding and DNA-based selection for plant improvement. In recent years, genomic approaches such as genome-wide association studies (GWAS) have been used to understand the genetic basis of important traits such as grain yield, disease resistance, and adaptation traits in wheat [1][2][3][4]. However, association mapping could not identify small effect loci and with such, the power of GWAS for the dissection of complex traits is limited [5,6].…”
Section: Introductionmentioning
confidence: 99%